Pengaruh Pemberian Beberapa Dosis Pupuk Organik Cair (Poc) Terhadap Pertumbuhan Bibit Kakao (Theobroma Cacao L.) - Aulia Meyuliana; Muharama Yora; Nur Salamah Harahap; Yuli Wahyu Eka Putri; Sri Rahmadina; Yelmi Wahyuni; Zulfi Marisa Elfian; Amalia Putri; Ica Safitri (Jurusan Budidaya Perkebunan, 2022)
This research aims to determine the effect of several doses of liquid organic fertilizer of tomatoes on the growth of cocoa nurseries. Cocoa nurseries need nutrients that support the growth of cocoa seedlings. Liquid organic fertilizer of tomatoes contains the nutrients needed for the growth of cocoa seedlings. This research method was carried out experimentally with 6 treatments of POC doses of a mixture of tomato extract, coconut water, and rice water, with 4 replications. he results of the study, it was explained that giving a dose of 25 ml of POC mixed with tomato extract, coconut water and ricE water/ 100 ml of water had a good effect on the growth and development of cocoa seedlings for the character of seedling height, number of leaves and leaf length. Furthermore, for the character of stem diameter, no significant effect was seen on the increased in stem diameter of cocoa seedlings. To overcome this, it is necessary to increased the dose of fertilizer or add other organic materials that can increases the diameter of the cacao seedlings.